THE CORRELATION BETWEEN RESIDENTIAL TYPE AND ECOLOGICAL AWARENESS OF STUDENTS IN HIGHER EDUCATION - Dipalaya, Tismi; Rahim, Abdurrachman; Fatma, Fatma (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study investigates the correlation between residential type (village, district, or city) and ecological awareness among students in higher education. Through a quantitative analysis, the research reveals that there are no statistically significant differences in ecological awareness across different residential backgrounds. The mean ecological awareness scores for students from villages, districts, and cities were 3.74, 3.81, and 3.70, respectively, suggesting that factors other than residential type may have a more substantial influence on ecological awareness. These findings challenge the strong version of place attachment theory, which posits that individuals in rural areas would have higher ecological awareness due to their closer proximity to nature. The study also notes the potential influence of other variables such as education level, media exposure, and personal values. Additionally, the research highlights the limitations posed by the small sample size, particularly for district residents, and calls for further studies with larger and more diverse samples to validate the findings. The results underscore the complexity of ecological awareness and the necessity of a multifaceted approach in understanding environmental attitudes and behaviors.